From the University to the Job Market: Graduates from Michoacana University (Mexico) - Zalapa Lúa, Elsa Edith (2019)
Job placement is highly regarded indicator among graduates, as is attaining accreditation among  higher education institutions. This study analyzes three dimensions of a survey conducted among graduates of the University of San Nicolás Hidalgo (UMSNH) in Michoacan, Mexico.  The survey objective was to learn what jobs graduates obtained, if any, upon graduation. This was a quantitative and descriptive study with a non-experimental design. Approximately 11,444 graduates were surveyed, 44.5% of which reported being unemployed while 50.2% were employed. It was determined that the main deterrent to securing a job was not having a college degree (30.2%) and the main asset to finding a job was matching the subject studies at university with the needs of the company (80%). Most graduates were employed by small businesses. Overall, UMSNH graduates report high job satisfaction, stating that their salary and hierarchical position represented was what caused the least job satisfaction. One can conclude from this type of study that universities and employers can work together to help university students enter the workforce upon graduation and help improve the current employer scenario.